Heterogeneous Impacts of Main and Feeder Road Improvements : Evidence from Ethiopia - Iimi, Atsushi; Mengesha, Haileyesus; Markland, James; Asrat, Yetmgeta; Kassahun, Kefargachew (World Bank, Washington, DC, 2018)
Rural access is among the most important infrastructure constraints in rural Africa. Using the results from comprehensive household surveys and other data from Ethiopia, the paper recasts light on the heterogeneous impacts of road accessibility on agriculture and nonagricultural growth. It is found that crop production is increased by major and feeder road improvements. Significant synergy is also found. When investigating further into this effect, there are two impacts: farmers' access to the input market, especially fertilizer, was improved mainly by major corridor improvement. And output market access was improved by feeder road improvement. In addition, the household's nonagricultural income is somehow increased by improved road connectivity. There must be secondary effects. The transport demand function estimated with additional data indicates that as the road network improves, people's mobility increases. Furthermore, local business employment is found to increase with road improvements. To meet the increasing demand for mobility, efficiency and frequency of transport services are important.